2020
DOI: 10.1038/s41598-020-61521-1
|View full text |Cite
|
Sign up to set email alerts
|

In-depth proteome analysis of more than 12,500 proteins in buffalo mammary epithelial cell line identifies protein signatures for active proliferation and lactation

Abstract: The mature mammary gland is made up of a network of ducts that terminates in alveoli. The innermost layer of alveoli is surrounded by the differentiated mammary epithelial cells (MECs), which are responsible for milk synthesis and secretion during lactation. However, the MECs are in a state of active proliferation during pregnancy, when they give rise to network like structures in the mammary gland. Buffalo (Bubalus bubalis) constitute a major source of milk for human consumption, and the MECs are the major pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…These DEPs were suggested to be related to metabolic, binding, and catalytic activities. Proteomic studies of buffalo mammary glands are relatively scarce; however, our group’s recent study identified 12,609 proteins in the in vitro grown proliferating BuMECs, using subcellular fractionation complexed with shotgun proteomics approach 30 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These DEPs were suggested to be related to metabolic, binding, and catalytic activities. Proteomic studies of buffalo mammary glands are relatively scarce; however, our group’s recent study identified 12,609 proteins in the in vitro grown proliferating BuMECs, using subcellular fractionation complexed with shotgun proteomics approach 30 …”
Section: Discussionmentioning
confidence: 99%
“…The pooled labeled peptides were fractionated using the Quaternary UHPLC system (Ultimate 3000, Thermo Scientific, USA) into 24 individual fractions as explained previously by Jaswal et al 30 Briefly, the pooled peptide sample was loaded onto the C18 column (4.6 × 250 mm, 5 ”m, Grace, USA) on a Dionex, UHPLC system. A total of 96 time‐based fractions were collected and further pooled into 24 individual fractions by mixing most hydrophobic with most hydrophilic based on concatenation approach (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic animal proteomics has also been applied to animal production systems related to different aspects of lactation. These included the study of lactating mammary epithelial cells in cattle and water buffalo [57,58], bovine milk proteome characterization and differentiation between breeds [59,60] or the establishment of protein biomarkers for early pregnancy diagnosis [61] estrus detection [62], male fertility [63,64].…”
Section: Domestic Animal Proteomics In India In Recent Yearsmentioning
confidence: 99%
“…In addition, workstations including solvent dispensing and computer‐controlled pressure gradients are highly valuable in saving time, consumables and costs while maintaining reproducible parallel preparation of up to 96 samples. As several deep proteome investigations have been published recently, 8,9 it is evident that the general need for high‐throughput methods has greatly increased also for proteomic investigations over recent years.…”
Section: Introductionmentioning
confidence: 99%